البيئة التنافسية وعلاقتها بأداء العمليات في المنظمة: بالتطبيق على الصناعات الغذائية، محلية أم درمان، ولاية الخرطوم،السودان،2019م - عبد الله, د. محمد احمد (Gezira Journal of Economic and Social Sciences; Vol 12 No 2 (2021), 2022)
هدفت هذه الدراسة إلى التعّرف على بعض عوامل البيئة التنافسية بالمنظمة وعلاقتها بالأداء العملياتي، وتمثلت مشكلة الدراسة في الكشف عن جوانب القوة والضعف النابعة من البيئة التنافسية وعلاقتها بأداء العمليات بالمنظمة، أتبعت الدراسة المنهج الوصفي التحليلي وذلك باستخدام برنامج الحزم الاحصائية للعلوم الاجتماعية SPSS وتوصلت الدراسة إلى النتائج التالية: وجود علاقة إحصائية بين البيئة التنافسية وأداء العمليات، حيث بلغت قيمة كاي0.74 عند مستوي الحرية 1 والقيمة الاحتمالية 00.1 وتشير إلى أن أداء العمليات يتأثر بالقوة التفاوضية بالمنظمة مع الجهة المسيطرة على المواد الخام ومستلزمات الانتاج، وكذلك الامكانات والموارد المتاحة بالمنظمة تمثل عنصر قوة في انسياب العمليات وسرعة التسليم إلا أن محدودية الطاقة الكهربائية وارتفاع تكاليف عوامل الانتاج شكلت نقطة ضعف في عملية الاداء بها، كما تمثل الجودة الشاملة والمعلومات والتكنولوجيا، وطريقة العمل والمعرفة اعتبارات هامة في تحسين أداء العمليات بالمنظمة، وأوصت الدراسة بضرورة القيام بعملية التحليل البيئي بصورة دقيقة ومنتظمة مع تبني استراتيجيات الترابط الأمامي والخلفي لسد النقص في الامداد وانسياب العمليات. This study aimed to identify some factors of the competitive environment in the organization and their relationship to operational performance, and the problem of the study was to reveal the strengths and weaknesses stemming from the competitive environment and their relationship to the performance of operations in the organization. The following: There is a statistical relationship between the competitive environment and the performance of operations, where the value of chi was 0.74 at the level of freedom 1 and the probability value 00.1. It indicates that the performance of operations is affected by the negotiating power of the organization with the party controlling raw materials and production requirements, as well as the capabilities and resources available in the organization represent an element of strength In the flow of operations and speed of delivery, however, the limited electric power and the high costs of production factors formed a weak point in the performance process, and the overall quality, information, technology, method of work and knowledge are important considerations in improving the performance of operations in the organization, and the study recommended the need to carry out the process of environmental analysis in an accurate and regular manner. With the adoption of forward and backward interconnection strategies to bridge the gap cut in the supply and the flow of operations.